The Effect of Ajwa Date (Phoenix dactylifera L., var. Ajwa) Phytonutrients in the Regulation of Male Reproductive Hormones (LH, FSH, Testosterone): A Literature Review - Mutiara Mutiara; Nasruddin Andi Mappaware; Nasaruddin Nawir (Journal of Community Health Provision, 2026)
Regulation of reproductive hormones is an important component of male reproductive health because it plays a crucial role in spermatogenesis, sexual function, and fertility. The balance of luteinizing hormone (LH), follicle-stimulating hormone (FSH), and testosterone is influenced by the integrity of the hypothalamic–pituitary–gonadal axis and the condition of the testicular microenvironment. Oxidative stress and inflammation are known to impair Leydig cell function and reduce the efficiency of steroidogenesis. Ajwa dates (Phoenix dactylifera L., var. Ajwa) are a natural food source rich in phytonutrients, including polyphenols and flavonoids, which exhibit antioxidant activity and protective effects on testicular tissue. This literature review aims to examine the role of Ajwa date phytonutrients in the regulation of male reproductive hormones, particularly LH, FSH, and testosterone. The method used was a literature review with a narrative review design, conducted through searches of the PubMed, Google Scholar, and ScienceDirect databases. The literature analyzed included experimental studies, clinical studies, and review articles published within the last ten years. Data were analyzed descriptively and narratively by grouping findings according to key biological mechanisms. The results indicate that phytonutrients from Ajwa dates and other parts of the date palm contribute to the reduction of oxidative stress and inflammation, improvement of testicular structure and function, and enhancement of testosterone production, with generally minimal changes in LH and FSH levels. In addition, under certain conditions, Ajwa dates show potential as hormonal modulators that help stabilize the balance of the hypothalamic–pituitary–gonadal axis. The conclusion of this review suggests that Ajwa dates have the potential to support the regulation of male reproductive hormones, although further clinical studies are still required.